St. Vincent and the Grenadines : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for St. Vincent and the Grenadines. (IMF Staff Country Reports; Country Report ;, 2021)
An explosive volcanic eruption that began on April 9 is hitting St. Vincent and the Grenadines hard, creating an urgent balance of payments need and a humanitarian crisis as the country continues to deal with the fallout from the global pandemic. The economy is estimated to have contracted in 2020 by 3.8 percent as tourism activity fell 70 percent. Before the eruption, economic growth was expected to be flat in 2021, as the global pandemic continued, and tourism remained depressed. While there is considerable uncertainty about the evolution of the eruption, staff estimate the infrastructure damage to exceed 20 percent of GDP and for the economy to contract by 6.1 percent in 2021 with agriculture and related sectors severely affected.